Cellulase enzyme production from Rhizophora mucronata - S.PRISCILLA HELEN CHRISTY; S.S.SUDHA (International Journal of Pharma and Bio Sciences, 2017)
Mangroves are important habitats seen at tropical and subtropical coastal regions. Endophytes are common in nature. Bacterial endophytes are less studied. In the present study, The Rhizophora mucronata sample was collected from coastal area of Thrissur district, Kerala. The bacteria was isolated from the sample by using pour plate technique and the bacteria was tested to produce cellulase by growing them on CMC agar medium for 1 day. It was screened by observing zones around the colonies. The bacteria was further identified using suitable biochemical tests. Then it was inoculated into cellulase production medium. Parameters like pH, temperature, incubation time were optimized. Enzyme activity was measured by DNS method at 540 nm. The results showed that the optimum temperature for cellulase enzyme production was 37°C, pH 8 and incubation period 48 hrs. The enzyme was partially purified by ammonium sulphate precipitation and dialysis. Finally characterized using SDS-PAGE analysis.